2018
DOI: 10.1111/trf.14574
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delayed umbilical cord clamping on public cord blood donations: can we help future patients and benefit infant donors?

Abstract: Our study indicates that DCC of 30 to 60 seconds has a small negative impact on collection of high-TNC-count CBUs. However, increasing BTC to more than 60 seconds decreases significantly both TNC content and volume, reducing drastically the chances of obtaining clinically useful CBUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Umbilical cord blood, which can only be collected at birth, has several practical considerations, such as banking safety, contamination, and identity and quality issues after long-term storage. There are several standardized operating procedures for obtaining clinically useful cord blood for future use to benefit infant donors [55], such as adhering to informed consent policies, financial disclosures, conflict-of-interest policies, and others [56] [57,58],. Stem cells from bone marrow has been widely studied in vitro and in animal models, but clinical trials have shown only limited effectiveness.…”
Section: (4) Reprogrammed Stem Cells Since 2006 Whenmentioning
confidence: 99%
“…Umbilical cord blood, which can only be collected at birth, has several practical considerations, such as banking safety, contamination, and identity and quality issues after long-term storage. There are several standardized operating procedures for obtaining clinically useful cord blood for future use to benefit infant donors [55], such as adhering to informed consent policies, financial disclosures, conflict-of-interest policies, and others [56] [57,58],. Stem cells from bone marrow has been widely studied in vitro and in animal models, but clinical trials have shown only limited effectiveness.…”
Section: (4) Reprogrammed Stem Cells Since 2006 Whenmentioning
confidence: 99%
“…20 There are appeals to limit DCC to no more than 60 seconds in populations at low risk for iron deficiency because longer clamping times could hamper cord blood banking. 13 However, the timing of cord clamping was 180 seconds or longer in 2 studies, 5,6 including the current study, demonstrating neurodevelopmental benefits in low-risk populations. Additional studies are necessary to determine optimal timing of cord clamping that would promote infant brain development and allow for cord blood banking.…”
Section: Timing Of Umbilical Cord Clamping and Infant Brain Developmentmentioning
confidence: 60%
“…12 60 seconds potentially allows transfusion of 40% more nucleated cells to the infant, compared with clamping within 60 seconds. 13 The type of milk (breastmilk vs formula) consumed during the first 3 months, as well as its nutrient composition, influence early myelination. 14 The authors mention that the mode of feeding was not different between groups, but do not provide details.…”
Section: Timing Of Umbilical Cord Clamping and Infant Brain Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed cord clamping (DCC) is currently a topic of interest in obstetrics literature, with noted benefits for both term and preterm infants. The American College of Obstetrics and Gynecology (ACOG) released a committee opinion recommending DCC for 30–60 seconds in vigorous term and preterm infants There is a concern for how DCC might affect the volume of umbilical CBU In line with the recommendations of ACOG our institution adopted a policy of 45 seconds of DCC for vigorous term and preterm infants in May of 2017, after the completion of this study. Prior to this policy being adopted, there was no standard practice regarding DCC at our institution; thus, we cannot comment on how DCC may have affected CBUV from either provider group.…”
Section: Discussionmentioning
confidence: 96%